ETIKA SOSIAL TERHADAP PARADOKS PERAN AGAMA DAN KEBEBASAN BERAGAMA DALAM KAITANNYA DENGAN KONFLIK DI INDONESIA - Trinovianto George Reinhard Hallatu (Universitas Musamus, Merauke, Papua, 2014)
Indonesia consists of various ethnic-groups, religions, races, etc which are the potential base of human resources. It could be created optimally if placed in equal aspiration framework then gives the great power. In the other side, the diversity has a potentialal to gives social crime-infested such as social conflict. Based on the view above, the writer writes this thesis entitled an observation of social ethics towards the paradox of religion role and freedom of religion in terms of conflicts in Indonesia.This is a descriptive qualitative research which for explain objectively and obviously regarding social ethics towards the paradox of religion role and freedom of religion in terms of conflicts in Indonesia.Conflicts happened in Indonesia lately caused by religion predicted. If it analyzed, religion is not a main cause of the conflicts happened in Ambon or other cities in Indonesia because every religion teaches kindness. Exclusives and excessive solidarity of some members of a religious community that cause conflicts among people. Based on ethics, the exclusives of some members leads to immoral behavior in terms of religion the worst thing. Specifically ethics focus on how people should life in relation with society to achieve security, safety and welfare. Ethics helps us not to loss orientation in transformation of culture, social, economy, politics and intellectual.Conflicts of religions that happened in Indonesia make freedom of religion concept is not appreciated as a human right. Religion should have a role to establish pluralism admit that every religion is legal and has value of righteousness.